Catalyst experiencing distinct reaction histories in one reactor bed results in coke of different properties in steam reforming. (1st June 2020) - Zhang, Zhanming; Zhang, Lijun; Gao, Zhiran; Sun, Kai; Shao, Yuewen; Zhang, Shu; Liu, Qing; Gao, Guanggang; Wei, Tao; Hu, Xun
Graphical abstract: Highlights: Catalyst of varied layer has varied reaction histories, impacting coking behaviors. Nickel size is lower in top-layer of catalyst bed, while coking was much higher. Coke on top-layer is carbon nanotubes with high thermal stability/crystallinity. Removal of the carbon nanotubes via combustion enhances nickel dispersion and the catalytic activity. Coke of bottom-layer is amorphous with less graphite-like structure and more defect. Abstract: The catalyst of varied location in a packed catalyst bed exposes to different reaction environments. How do this affect the catalytic behaviors such as resistivity to coking was investigated in this study by dividing the catalyst bed of a fixed-bed reactor into three-layers, aiming to understand the correlation of reaction histories of different layer of catalyst with properties of coke. The particle sizes of metallic species in top-layer catalyst were the lowest while the highest in bottom-layer catalyst, due to the endothermic characteristics. Nevertheless, coking was further more serious on top-layer catalyst. The reactions occurred on the top-layer catalyst involved the homogenous decomposition/polymerization of the organics, the absorption and activation of the abundant organic reactant, the formation of carbonaceous reaction intermediates from dissociation of the organics, etc. This changed the composition of the reaction mixture and affected the reaction network in the bottom-layer catalysts, leading to the varied properties of coke. The coke in the top-layer catalyst was the more thermal stable carbon nanotubes with more graphite-like structure while that in bottom-layer catalysts were amorphous coke. The removal of the carbon nanotubes enhanced nickel dispersion and catalytic performance, while such effects were not observed in removal of the amorphous coke.